2003
DOI: 10.1099/ijs.0.02323-0
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio hydrothermalis sp. nov., a novel sulfate-reducing bacterium isolated from hydrothermal vents

Abstract: T ) differed from D. zosterae not only phylogenetically, but also genomically (DNA-DNA reassociation value between the two bacteria was 23?8 %) and phenotypically. This isolate is therefore proposed as the type strain of a novel species of the genus Desulfovibrio, Desulfovibrio hydrothermalis sp. nov.Deep-sea hydrothermal vents are among the most productive ecosystems on Earth, where unusual animal and microbial communities are able to survive the harsh combinations of toxic chemicals, high pressures, high tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 30 publications
0
55
1
Order By: Relevance
“…T , in comparison with those of closely related species of the genus Desulfovibrio, are shown in Table 1 and were determined as described previously (George et al, 2008;Alazard et al, 2003).…”
Section: Strain Rb22mentioning
confidence: 99%
“…T , in comparison with those of closely related species of the genus Desulfovibrio, are shown in Table 1 and were determined as described previously (George et al, 2008;Alazard et al, 2003).…”
Section: Strain Rb22mentioning
confidence: 99%
“…Although the biodiversity of sulfur-reducers has been widely studied in these deep ecosystems, there are few reports on the isolation and characterization of sulfate-and/or sulfite-reducers (Alazard et al, 2003;Burggraf et al, 1990;Elsgaard et al, 1995;Huber et al, 1997;Jeanthon et al, 2002;Rueter et al, 1994). Here, we describe a novel thermophilic sulfate-reducer (strain T revealed that this novel isolate groups with members of the family Desulfohalobiaceae (Kuever et al, 2003) in the d-subclass of the Proteobacteria and is related to Desulfonatronovibrio hydrogenovorans (similarity 86?5 %) (Fig.…”
Section: Microscopic Observations Revealed That Cells Of Strain 6nmentioning
confidence: 99%
“…However, the dominance of sulfate-reducing bacteria in hydrothermal communities has been confirmed by measurements of sulfate-reduction activity in sediments (Elsgaard et al, 1994;Jorgensen et al, 1992) and by their repeated isolation from hydrothermal samples (Alazard et al, 2003;Elsgaard et al, 1995). Thermophilic sulfate-and/or sulfite-reducing members of the domain Archaea were found to be representative of these deep microbial communities.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…strain LVform6 isolated from carbonate sediments (Van Lith et al, 2003), and to the recently described species 'Desulfovibrio capillatus' (98?2 % similarity), isolated from an oilfield separator (Miranda-Tello et al, 2003). Since it is also closely related to Desulfovibrio longus (97?5 % similarity), the results of Postgate (1984), Esnault et al (1988), Caumette et al (1991), Magot et al (1992), Tardy-Jacquenod et al (1996a), Bale et al (1997), Krekeler et al (1997), Motamedi & Pedersen (1998), Nielsen et al (1999), Alazard et al (2003) and Miranda-Tello et al (2003). +, Positive test reaction; (+), weak test reaction; 2, negative test reaction; ND, not determined.…”
mentioning
confidence: 92%